2012
DOI: 10.1088/1757-899x/38/1/012003
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Orbit Gaps in Armchair Nanotubes Calculated Using the Linear Augmented Cylindrical Wave Method

Abstract: Comparative analysis of the electronic structures of mono-and bi-atomic chains of IV, III-V and II-VI group elements calculated using the DFT LCAO and LACW methods P. N. Abstract. In the terms of the muffin-tin and local density functional approximations, a relativistic version of linear augmented cylindrical wave method is developed and applied to calculating the gaps in the Fermi energy region induced by the spin-orbit coupling in the armchair tubules (n, n) (where 4 ≤ n ≤ 12). Due to the spin-orbit interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The calculations of integrals true〈ΨP2M2N2(r|kL)χ2false|HSOfalse|ΨP1M1N1(r|kL)χ1true〉 with the H S–O operator Eq. is facilitated by the fact that the basis functions ΨPMN(r|kL) are the products of radial functions and spherical harmonics in the MT regions . The final equation obtained here to calculating these integrals are presented below false〈ΨP2M2N2(r|kL)αfalse|HSOfalse|ΨP1M1N1(r|kL)αfalse〉=n2c2h(1)nfalse(M1+M2false)αMT=1,2false(rαMTfalse)4l=0false(2l+1false)m=llmfalse(lfalse|mfalse|false)!false(l+false|mfalse|false)!×false{ς…”
Section: Methods Of Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculations of integrals true〈ΨP2M2N2(r|kL)χ2false|HSOfalse|ΨP1M1N1(r|kL)χ1true〉 with the H S–O operator Eq. is facilitated by the fact that the basis functions ΨPMN(r|kL) are the products of radial functions and spherical harmonics in the MT regions . The final equation obtained here to calculating these integrals are presented below false〈ΨP2M2N2(r|kL)αfalse|HSOfalse|ΨP1M1N1(r|kL)αfalse〉=n2c2h(1)nfalse(M1+M2false)αMT=1,2false(rαMTfalse)4l=0false(2l+1false)m=llmfalse(lfalse|mfalse|false)!false(l+false|mfalse|false)!×false{ς…”
Section: Methods Of Calculationsmentioning
confidence: 99%
“…The LACW method is an extension to the tubular structures of the augmented plane wave (APW) theory suggested by Slater in 1937 for crystals and developed latter in a form of linearized APW (LAPW) technique . Taking into account only translational symmetry, the LACW approach with SO coupling was used previously to calculate the SO gaps in a Fermi energy region of armchair CNTs and to refine the electron bands of structurally very simple case of linear carbon chains (carbynes) . The method developed here takes into account also the screw and rotational symmetries of CNTs and can be applied to any CNT independent on chirality or a number of atoms in translational cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of a spin‐orbit (SO) interaction, the double orbital and double spin degeneracy should yield the fourfold degenerate electronic levels. In papers, we calculated the SO gaps in the Fermi energy region for the metallic ( n , n ) tubules and for the metallic and semiconducting linear carbon chains (carbynes). These cases are very interesting, because a formation of gap between the occupied and unoccupied bands is purely relativistic effect here.…”
Section: Spin‐orbit Couplingmentioning
confidence: 99%
“…The Lz, L± operators do not perturb the radial part of the wave function, and the integral ΨP2M2N2ktrue(boldrtrue)χ2|HSO|ΨP1M1N1ktrue(boldrtrue)χ1 takes the form of product of the radial and angular parts simplifying calculation of these matrix elements, which are presented in papers …”
Section: Spin‐orbit Couplingmentioning
confidence: 99%
“…In terms of the kp- method, it was shown that the curvature of the nanotube surface breaks a symmetry that is present in graphene; this broken symmetry enhances the intrinsic spin–orbit coupling in carbon nanotubes compared with flat graphene, and the spin–orbit term gives rise to the splitting of energy levels and formation of gaps about 0.1 meV. The curvature-induced spin–orbit splitting in the Fermi level region of nanotubes was also studied in terms of the empirical tight-binding models, in addition to the first-principle projected augmented wave and linear augmented cylindrical wave methods . The spin–orbit effects were also qualitatively studied in the curved graphene, fullerene, and nanotube caps in terms of simple π-electron model and perturbation theory, the importance of curvature of a carbon material surface for larger spin–orbital coupling being indicated again .…”
Section: Introductionmentioning
confidence: 99%